IMPLEMENTASI PROGRAM LEDIG (LEBU DIGITAL) DALAM MENINGKATKAN PELAYANAN PUBLIK DI DESA CANGKINGAN KECAMATAN KEDOKANBUNDER KABUPATEN INDRAMAYU - Lurhfi Faisal Natsir; Ismanudin; Rizki Ilham Juliansyah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The Ledig Program is an excellent program from the Indramayu Regent, the problems found in this program are the limited human resources and financial resources in Cangkingan Village, that the transition of services from manual to digital is not a small cost in addition to changing the mindset of village officials. With the problems that have been mentioned, the researcher has the aim of analyzing the Implementation of the Ledig Program in improving public services in Cangkingan Village. The research method used is descriptive qualitative. In the implementation of the Ledig Program in improving public services, Cangkingan Village has made self-service for residents who want to get services online and the results will be directly delivered by village officials to the applicant's home. In addition, with the Ledig Program, Cangkingan Village has developed online facilities by creating an “online lapak” marketpalce for villagers who are registered to have MSME businesses. The obstacle to implementation is that all digital development is charged to Village Fund sources, which is a challenge for the Cangkingan Village Head, where the budget is limited and not only for digitalization developers.